Design and Implementation of Washing-Filling-Capping Machine for Small-Scale Reverse Osmosis Water Industry. (April 2020) - Ahmad, N U; Miskon, M T; Katon, M Z; Ibrahim, N; Ismail, R; Mohamed, H
Abstract: This paper discusses the design and development of a semi-automated washing, filling and capping machine for 5-gallon bottle used by local reverse osmosis water (RO) refilling supplier. The problem facing by the local supplier is low production capability of RO water as the washing to capping processes were done manually, which were time and energy consuming. This manual procedure also caused back pain and fatigue to the staff. The objective is to design and develop a semi-automated machine (3-in-1 machine) which involves a washing-rinsing module to clean the external and internal of three 5-gallon-bottles simultaneously, a RO water filling module and a bottle capping module. The effluent of filtered RO water is collected and used as the source water for bottle washing-rinsing process. This helps to optimize the water usage. The results show that the productivity of supply has improved. The production per hour has increased by 52.3%. The production cost per unit of bottle has reduced by 28%. The new machine has successfully operated, improving the productivity and ergonomically designed to minimize physical discomfort to the staffs.